Slow Traffic, Fast Food: The Effects of Time Lost on Food Store Choice - Panka Bencsik; Lester Lusher; Rebecca L.C. Taylor (Institute of Labor Economics (IZA), 2023)
Time scarcity is one of the strongest correlates of fast food consumption. To estimate the causal effect of time lost on food choice, we match daily store-specific foot traffic data traced via smartphones to plausibly exogenous shocks in highway traffic data in Los Angeles. We find that on days when highways are more congested, individuals are more likely to dine out and less likely to grocery shop. The effects are particularly pronounced for afternoon rush hour traffic. Our results imply a net reduction in healthy food store choice due to time lost.
Keywords: I12; I30; J22; R41; 330; traffic congestion; time constraints; store choice; nutrition; fast food